Quantum and electrochemical studies of the hydrogen evolution findings in corrosion reactions of mild steel in acidic medium - Zohdy, K.M.; El-Sherif, Rabab M.; Ramkumar, Sowmya; El-Shamy, A.M. (Upstream Oil and Gas Technology, 2021)
•The successful corrosion levels and the degree of the proliferation of hydrogen improved with enhanced atmospheric temperature or reduced concentration of the inhibitor.•The overall surface film resistance decreased as the inhibitor content decreased suggesting a decline in steel corrosion rate.•The GABA behaved as an effective green corrosion inhibitor and demonstrated a very high inhibition efficiency at a concentration of 0.5 M H2SO4 solution hitting 92.4 percent.•The measurement of EHOMO, ELUMO, the energy gap (∆E) and the segment of transported electrons (∆N) showed GABA's inhibition power. The electrochemical techniques included electrochemical impedance spectroscopy (EIS) and Tafel polarization. Changing GABA concentrations greatly impacted the rate of both the corrosion reaction and the evolution of hydrogen. The findings of polarization suggested that GABA is a mixed inhibitor of form. Rising the temperature (298–338 K) resulted in an intensification in the rate of hydrogen progression and a diminution in their steel's full superficial confrontation measure (RT) or comparative coverage width (1/CT). The inhibition capacity of GABA was demonstrated by the quantity control including EHOMO, ELUMO, the energy gap (∆E) and the segment of relocated electron (∆E). Optimized goemetry, chrage distribution and molecular orbital plots and the active sites for electrophilic and nucleophilic attack on GABA. [Display omitted]